Cumulation and antidumping: A challenge to competition - Thomas J. Prusa (Rutgers University, Department of Economics, 1998)
Competition policy emerged as an important area of interest during the later stages of Uruguay Round negotiations. The task of establishing competition policy is complicated by the fact that there already are trade statutes—antidumping, countervailing duty, safeguard actions—that relate to issues of competition. Interestingly, the existing trade statutes often seemed designed to reduce the effect of foreign competition on domestic producers. The tension between the existing trade statutes and competition policy is most probably most clearly evidenced by antidumping law, the most widely used trade statute. In this paper I will concentrate on how one specific amendment, the cumulation provision, clearly makes AD an anti-competitive law and exemplifies the challenges that face those policy-makers who hope to move toward to an economically justified competition policy. Evidence will show that cumulation has led to more multiple petition filings and to smaller competitors being named. I will also argue that cumulation has changed the outcome (from negative to affirmative) in dozens, and possibly hundreds, of cases. Given all of these effects, cumulation should be viewed as a significant obstacle to those interested in assimilating AD law into the broader notion of competition policy.
Keywords: F1; 330; antiduming; competition; cumulation